Perinatal Outcomes Associated with Latency in Late Preterm Premature Rupture of Membranes - Choi, Eui Kyung (Int J Environ Res Public Health, 2021)
This study aims to evaluate the perinatal outcomes of preterm premature rupture of membrane (PPROM) with latency periods at 33 + 0–36 + 6 weeks of gestation. This retrospective case-control study included women with singleton pregnancies who delivered at 33 + 0–36 + 6 weeks at Korea University Ansan Hospital in South Korea between 2006–2019. The maternal and neonatal characteristics were compared between different latency periods (expectant delivery ≥72 h vs. immediate delivery <72 h). Data were compared among 345 women (expectant, n = 39; immediate delivery, n = 306). There was no significant difference in maternal and neonatal morbidities between the groups, despite the younger gestational age in the expectant delivery group. Stratified by gestational weeks, the 34-week infants showed a statistically significant lower exposure to antenatal steroids (73.4% vs. 20.0%, p < 0.001), while the incidence of respiratory distress syndrome (12.8%) and the use of any respiratory support (36.8%) was higher than those in the 33-week infants, without significance. Our study shows that a prolonged latency period (≥72 h) did not increase maternal and neonatal morbidities, and a considerable number of preterm infants immediately delivered at 34 weeks experienced respiratory complications. Expectant management and antenatal corticosteroids should be considered in late preterm infants with PPROM.